Anti-COVID-19 Credentials of Chitosan Composites and Derivatives: Future Scope? - Judy Gopal; Manikandan Muthu; Suraj Shiv Charan Pushparaj; Iyyakkannu Sivanesan (MDPI AG, 2023)
Chitosan derivatives and composites are the next generation polymers for biomedical applications. With their humble origins from the second most abundant naturally available polymer chitin, chitosan is currently one of the most promising polymer systems, with wide biological applications. This current review gives a bird's eye view of the antimicrobial applications of chitosan composites and derivatives. The antiviral activity and the mechanisms behind the inhibitory activity of these components have been reviewed. Specifically, the anti-COVID-19 aspects of chitosan composites and their derivatives have been compiled from the existing scattered reports and presented. Defeating COVID-19 is the battle of this century, and the chitosan derivative-based combat strategies naturally become very attractive. The challenges ahead and future recommendations have been addressed.